Technology and science education: Looking at the future - Beatriz Amante García; María Martínez Martínez (OmniaScience, 2016)
As usual in JOTSE, the first editorial of the year presents an analysis of our Journal evolution. In this sense, we reflect on the changes undergone and the challenges we will face in the new year 2016.